forage Yields of Cenchrus ciliaris and Lasiurus sindicus Grown in Association with Trees under Arid Conditions - Sharma, B. M.; Gupta, J. P.; Rathore, S. S. (Indian Forester, 1998)
Field trials conducted at Central Arid Zone Research Institute, Jodhpur, for seven consecutive years (1988 to 1994) revealed that yields of Cenchrus ciliaris and Lasiurus sindicus grown in association with trees were lower than the yields of sole grasses. The changes in height of Acacia tortilis and Zizyphus rotundifolia were also more under the control. The height of trees decreased in association with grasses. The average soil moisture stored in the 90 cm profile under A. tortilis was lower as compared to Z. rotundifolia. Moisture storage decreased further when the grasses were grown with the trees. Organic matter increased over the initial level in all tree-grass combinations. The uptake of P by the two grasses alone or in combination with trees, was marginally different. While the uptake of Ca, Mg and K was considerably higher by L. sindicus than C. ciliaris.